Effect of Foeniculum Vulgare And Metoclopramide On The Carbohydrate And Protein Levels Of The Mammary Glands In Lactating White Mice - Awad, Reem Saleh; Ali, Israa Hashim (Journal of Neonatal Surgery, 2025)
Background: Galactagogues are chemical treatments, foods, or herbal supplements known to stimulate, support, and enhance breast milk production. Women can use these galactagogues to stimulate, increase, or maintain milk production. Aim of the study: This study aimed to investigate the effect of both Foeniculum vulgare and metoclopramide on the development of mammary glands of lactating mice by using 2 type of staining Schiff's reagent (PAS) stain and Mercuric bromophenol blue (MBB). Material and method: The research ran from October 27, 2024, until January 27, 2025, at Tikrit University's College of Science and the animal house of the College of Veterinary Medicine. Eighty female mice were used in the experiment for 20 days and divided into four groups, each group contain 20 rats as follows: T1 (control group): lactating females were given normal food and water. T2: lactating females were given 10% Foeniculum vulgare. T3: lactating females were given 2 mg of metoclopramide. T4: lactating females were given 10% Foeniculum vulgare and 2 mg of metoclopramide . Result: The Foeniculum vulgare used in the study contain the compounds Anethole, Fenchone, Estragole, Limonene, α-Pinene and Linalool at concentrations of 39.27, 9.30, 8.60, 5.43, 4.34 and 4.68 mg L-1, respectively. By using two type of staining, the histopatological section showed the group dosed with Foeniculum vulgare and metoclopramide, the reaction was positive, and high purple staining was observed, indicating the severity of the reaction, ​​in addition, the purity of the stain was clearly evident in some sections of the alveoli, especially the large ones. Conclusion: Foeniculum vulgare and metoclopramide have Synergic effect on mammary gland which increase alveolar secretions than control